Flujos migratorios africanos en Costa Rica (2014-2020) - Navarro Alvarado, Guillermo Antonio (El Colegio de México, 2022)
The following article analyzes the quantitative dimensions of African migratory flows in Costa Rica, their composition, forms of representation, and conditions of possibility between 2014 and 2020. It examines secondary sources and annual data from the General Directorate of Migration and Alien Affairs of Costa Rica (DGME) and the Temporary Assistance Centers for Migrants (CATEM). The article concludes that these migratory flows are defined by broad cultural diversity with multiple origins, characterized by the migratory presence of all the African subregions, with the greatest migration being from Central Africa. Representation of this diversity is limited by the use of homogenizing categories such as “extracontinental” and raises the need for specific studies.